1995
DOI: 10.2466/pr0.1995.76.3c.1107
|View full text |Cite
|
Sign up to set email alerts
|

Prejudice toward Persons Living with a Fatal Illness

Abstract: Vignettes depicting a person living with a fictitious fatal illness were presented to 222 undergraduates. Manipulated variables in a completely randomized 3 x 2 x 2 factorial design were method of transmission of the illness (genetic/contagious/infectious), the population likely to become ill (anyone/primarily marginal persons), and the amount of suffering (little/much). Subjects reported on perceptions of ease of transmission of the illness, danger of contact with the ill person, blame, support of sanction, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Blame attribution reveals four factors that explain how publics attribute blame to groups and organizationsa litmus testof clear association, low commitment to the issue, competence to solve the problem, and material blame. A study has showed that when the illness is contagious, people with this illness are likely to be blamed as it is perceived as a great danger of contact (Dukes & Denny, 1995). Moreover, people with illness such as obesity are more likely to be stigmatized and blamed for their own problems (Hoyt et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Blame attribution reveals four factors that explain how publics attribute blame to groups and organizationsa litmus testof clear association, low commitment to the issue, competence to solve the problem, and material blame. A study has showed that when the illness is contagious, people with this illness are likely to be blamed as it is perceived as a great danger of contact (Dukes & Denny, 1995). Moreover, people with illness such as obesity are more likely to be stigmatized and blamed for their own problems (Hoyt et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, when medical staff (or members of the general public) engage in victim blaming of the ill, it is often directed at patients who are overweight, who smoke or who have otherwise put themselves at risk of damaging their own health (e.g. Dukes and Denny 1995). Further contributing to this blaming of the ill is our automatic tendency to underestimate the probability that either our families or we will contract a particular illness (Taylor and Brown 1988).…”
Section: The Behaviour Of Hospital Staffmentioning
confidence: 95%
“…26 27 This happens most often when risky behaviour was involved in the misfortune, as in the case of Julian's leg and John's streptococcal infection, but it also happens in cases where there was no risk. 28 To blame a person for a random misfortune, for which they are not responsible, is unjust. We are not responsible for diseases or injuries that we did not cause: but we are responsible for the suffering that we knowingly bring upon ourselves.…”
Section: Anger and Desertmentioning
confidence: 99%